INDUKSI TRICODERMA SP DAN PAENIBACILLUS POLYMYXA TERHADAP KETAHANAN PENYAKIT BLAS DAN KRESEK PADA PRODUKTIVITAS TANAMAN PADI (ORYZA SATIVA L.) - Elfin Efendi, S.TP., MP; Zunaida Sitorus, S.Si., M.Si; Rahmadi Rajab, SP (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
The reseach was conducted in Panca Arga Village, Rawang Panca Arga District, Asahan, North Sumatra, to determine the effect of Trichoderma sp. and Paenibacillus polymexa induction on rice blast and kresek disease resistance. The study used a factorial randomized block design with two factors: four levels of Trichoderma sp. concentration: T0 0 ml/liter, T1 25 ml/liter, T2 50 ml/liter, T3 70 ml/liter, and three levels of Paenibacillus polymexa bacteria: P0 0 ml/liter, P1 50 ml/liter, P2 100 ml/liter, with three replications. Observation parameters included plant height, number of tillers, flowering age, intensity of blast disease attacks, intensity of kresek disease attacks, harvest age, production per clump, and production per plot. The results showed that Trichoderma sp induction gave the best results at a plant height of 90.80 cm, the number of tillers was 30.58 plants, flowering age was 46.08 days, blast attack intensity was 0.51%, kresek attack intensity was 3.63%, harvest age was 110.72 days, production per clump was 64.78 g and production per plot was 1.61 kg. Paenibacillus polymyxa induction gave the best results at a plant height of 85.88 cm, the number of tillers was 30.15 plants, flowering age was 45.81 days, blast attack intensity was 4.20%, kresek attack intensity was 4.40%, harvest age was 110.31 days, production per clump was 61.25 g and production per plot was 1.54 kg. The interaction between Trichoderma sp and Paenibacillus polymyxa induction had no significant effect on plant height, number of tillers, flowering age, harvest age, production per clump, and production per plot. The interaction had a significant effect on the intensity of blast and kresek attacks